Implementasi Metode Single Exponential Smoothing Dalam Memprediksi Kebutuhan Pupuk Bagi Petani - Oktaviani Dwi Rahayu; William Ramdhan; Sumatri Sumatri (Building of Informatics, Technology and Science (BITS), 2022)
CV. Bima Agung Sejati, Air Batu District sells various types of fertilizers needed by farmers. From year to year fertilizer needs for farmers in CV. Bima Agung Sejati, Air Batu District, is experiencing a shortage and excess stock of goods. This is due to stock procurement without predicting needs in advance. The aims of study are to apply the Single Exponential Smoothing method to the forecasting system in determining fertilizer needs for farmers on CV. Bima Agung Sejati, Air Batu District, then designed the forecasting system using the Visual Basic 2010 programming language and the database uses MySQL. the method used by researchers in conducting research and use in the process of analyzing data is the Single Exponential Smoothing (SES) method. The results of the implementation of this method show predictions in the next period counting Naga Mas as many as 709.59, Gaja Mas as many as 590.56, Rabbit Mas as many as 814.60. This forecasting yields with an average MAPE below 6%. Thus the use of forecasting results with the SES method is worthy of being used as a reference for good stock procurement in CV. The True Great Milky Way in the later period. In addition, calculations have been carried out systematically which makes it easier for the store to calculate quickly and easily